Study of genetic parameters on the weight performance of Caracu cattle (Research, Society and Development, 2022)
The objective was to obtain estimates of heritability and genetic trends of Caracu cattle on body weight variables. The animals belonged to the state of Mato Grosso, with information on birth weights, age-adjusted weights at 240, 500, 830 days of age. Contemporary groups were formed by combining the fixed effects of year and time of weighing and animal sex. For the estimation of variance components, mixed linear models were used with fixed effects of contemporary groups, random effects, additive genetics, maternal genetics (for pre-weaning weights) and residual, using the restricted maximum likelihood method and the equations of mixed models. for the prediction of genetic values. Genetic trends were estimated through linear regression of the genetic values of the animals as a function of the year of birth, for males and females, separately. Direct heritability estimates ranged from 0.24 to 0.45 for all weights, demonstrating the presence of genetic variability. Genetic trends were estimated for birth weight of -0.169 and -0.016, weaning weight of 0.117 and 0.138, yearling weight of 0.430 and 0.341 and adult weight of -0.541 and -0.176 kilograms per year, respectively, for males and females. The heritabilities and the genetic tendency indicated that, in the face of direct selection for ponderal traits, an expected response for the Caracu breed was obtained, denoting an increase in growth speed in the rearing and evidencing weaning as a selection criterion.